2011 Libyan uprising and NATO intervention: A critical analysis - Musa, Basiru; Yaacob, Che Mohd Aziz; Omar, Rusdi (2016)
The study critically evaluated the impact of NATO’s military intervention in the 2011 Libyan uprising.Specifically, it was intended to protect innocent civilians by imposing a no-fly zone over Libya ordered by a United Nations Security Council Resolution: 1973 or it was carried out to further the global hegemonic interests of the US through NATO’s military might.The work utilised a theoretical framework of Collective Security, developed by A.F.K. Organski in 1958, and relied on documentary method of data collection and thematic analysis as its tool or yardstick for data analysis.It was found out that the enforcement of a no-fly zone over the Libyan airspace did not protect innocent civilians, but resulted in toppling of Muammar Gaddafi and his 42 year old regime (1st September, 1969-20th October, 2011), worsening insecurity, fragile and unstable government, proliferation of weapons in Libya and its neighbours, such as Mali and Egypt, Diplomatic failure, Loss of Libya’s internal and external sovereignty, aiding the rebels to victory over Gaddafi, decimation of the hitherto stable Libyan society and plunging it into utter anarchy, shattering of the Libyan economy and its endowed oil wealth.Therefore, this brings to the fore, the apparent need for a truly autonomous, robust and impartial Global Authority to check the excesses of the super-ordinate states, such as US, France, Britain and their allies so as to protect weaker states in the global system from the catastrophic drawbacks of an unnecessary military intervention, which has an ulterior imperialist motive.Libya is today a shadow of its former prosperous and stable self under Gaddafi and the hope of stability, peace and sustainable human development continues to fade.